Surgical Challenges in Multi-Vessel Minimally Invasive Coronary Artery Bypass Grafting - Jia-Ji Liu; Qing-Yu Kong; Bin You; Lin Liang; Wei Xiao; Xiao-long Ma; Feng Pan; Li-Qun Chi (Journal of Interventional Cardiology, 2021)
Objectives. Minimally invasive coronary artery bypass grafting (MICS CABG) has emerged as an alternative treatment for patients with multi-vessel coronary artery disease, but there are certain surgical challenges inherent in the adoption of this approach. The present study was conducted to provide insight regarding the outcomes associated with our first 118 cases, to discuss the surgical difficulties encountered in these patients, and to outline the potential countermeasures. Methods. Between January 2017 and January 2020, 118 patients underwent multi-vessel MICS CABG. These patients were stratified into two groups based upon whether they did or did not experience surgical challenges, and early clinical outcomes were compared between these groups to assess the incidence of technical difficulties and associated factors. Results. Surgical challenges arose in 38 of the 118 cases in this study, including 13 cases of exposure-related difficulties, 11 cases of proximal anastomosis-related difficulties, 15 cases of distal anastomosis-related difficulties, 4 cases of LITA-related difficulties, and 3 cases of lung-related difficulties. Relative to the other 80 patients, those patients for whom intraoperative technical challenges arose experience significant increases in operative duration (4.94 ± 0.89 vs. 5.59 ± 1.11 h, P=0.001), intraoperative blood loss (667 ± 313 vs. 892 ± 532 mL, P=0.005), length of the ICU admission (17.59 ± 3.51 vs. 22.59 ± 17.31 h, P=0.015), and the duration of postoperative hospitalization (5.96 ± 1.23 vs. 6.71 ± 1.92 days, P=0.012). There were no significant differences between these groups with respect to the mean graft number, major complications such as stroke or organ dysfunction, or one-year graft patency. Conclusions. There is a substantial learning curve associated with performing off-pump MICS CABG to treat multi-vessel disease. Surgical challenges encountered during this procedure may increase the operative duration, intraoperative blood loss, ICU admission, and the duration of postoperative hospitalization. However, these issues do not appear to compromise the efficacy of complete revascularization, and early clinical outcomes associated with this procedure remain acceptable.